2009
DOI: 10.1007/s10571-008-9343-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Lithium in Ameliorating the Aluminium-induced Oxidative Stress and Histological Changes in Rat Brain

Abstract: This study was carried out to investigate the effects of lithium (Li) supplementation on aluminium (Al) induced changes in antioxidant defence system and histoarchitecture of cerebrum and cerebellum in rats. Al was administered in the form of aluminium chloride (100 mg/kg b.wt./day, orally) and Li was given in the form of Li carbonate through diet (1.1 g/kg diet, daily) for a period of 2 months. Al treatment significantly enhanced the levels of lipid peroxidation and reactive oxygen species in both the cerebru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 48 publications
(56 reference statements)
8
33
0
Order By: Relevance
“…Previous studies showed that MPH at highest therapeutic doses used can decrease SOD and GPx activities in rat hippocampus (Motaghinejad, Motevalian, 2015e). It has been proven that lithium is capable of modulating the oxidant-antioxidant activities and therefore showing the neuroprotective effects (Bhalla and Dhawan, 2009). Overall, our study showed that treatment with Lithium (150mg/kg) alone causes decrease in MDA ,GSSG and increase in GSH content and SOD and GPx activities which is statistically significant when compared to MPH only treated group and was not significant compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that MPH at highest therapeutic doses used can decrease SOD and GPx activities in rat hippocampus (Motaghinejad, Motevalian, 2015e). It has been proven that lithium is capable of modulating the oxidant-antioxidant activities and therefore showing the neuroprotective effects (Bhalla and Dhawan, 2009). Overall, our study showed that treatment with Lithium (150mg/kg) alone causes decrease in MDA ,GSSG and increase in GSH content and SOD and GPx activities which is statistically significant when compared to MPH only treated group and was not significant compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons which make nervous system organs more susceptible include; high oxygen uptake, neuronal membrane lipids rich in polyunsaturated fatty acids, modest antioxidant defence and several auto-oxidizable neurotransmitters. Therefore, in situations such as MTX administration where the generation of free radicals exceeds, the capacity of anti-oxidant defence, oxidative stress may lead to membrane degradation and cellular dysfunction (Bhalla and Dhawan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This elevation in MDA may be due to that GA 3 is associated with generation of ROS which interacts with tissues leading to numerous pathophysiological alterations (Yu et al 2008). ROS could damage every major cellular component, including membranes, lipids, carbohydrates and DNA (Bhalla and Dhawan 2009). So, GA 3 treatment might cause peroxidation of polyunsaturated fatty acids leading to the cellular deterioration (Troudi et al 2011).…”
Section: Discussionmentioning
confidence: 99%